b - 9 (b, 2020)
Contributed articles on Anwarullah Chowdhury, college teacher and educator from Bangladesh; commemorative volume.
In Bengali.
Keywords: 9; College teachers -- Bangladesh -- Biography; Educators -- Bangladesh -- Biography